Afforestation and wastelands development some success stories - National Afforestation and Eco-development Board (Bangalore, 1994)
The NAEB and NWDB have been providing grants to these registered Non Government Organisations for activities related to tree planting, wastelands develop ment and regeneration of degraded forest areas. Many NGOs/Voluntary Agencies and other registered non-profit organisations in South India have received financial assistance from NAEB/NWDB under Grant-in-aid scheme and have implemented many afforestation and wastelands development programmes in recent years. Some of them have achieved considerable success in their programmes in the areas of creating awareness among people, involving people in development process, tree planting, raising seedlings, afforestation, development of wastelands and regeneration of degraded forest areas. Many a times such achievements go un documented. Therefore, it is important to know, how some of these organisations have been successful in their work, in order to draw some inferences and design strategies for achieving better success in the future endeavours. In this background. the Ministry of Environment and Forests, Government of India, has suggested to this centre to undertake a study of selected successful organisations in South India and to publish such 'Success Stories'.
Keywords: Land reforms